The Alienation of West Manggarai Regency Government Land by Third Parties Through Sale and Purchase (Study of the Kupang High Court Decision, Number 13/Pid.Sus-TPK/2021/PT.Kpg) - Rizki Dwi Haryani; Fransiscus Xavierius Arsin Lukman (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The aim of this research is to analyze the procedure for transferring land belonging to the West Manggarai Regency Government through buying and selling, whether it is in accordance with applicable laws and regulations and the legal consequences of transferring rights to land belonging to the regional government carried out by a third party through buying and selling. To answer this problem, a normative juridical legal research method is used by examining all statutory regulations related to the problem under study. The research results show that the procedure for transferring land belonging to the West Manggarai Regency Government can be carried out by selling in the form of auction, exchange, grant or regional government capital participation accompanied by land appraisal and requesting DPRD approval first. Buying and selling cannot be carried out to transfer regional property because it is not in accordance with what is regulated in Article 82 Paragraph (2) of Regional Regulation 11/2017. The legal consequences of the transfer of land by the Government of West Manggarai Regency through buying and selling, resulted in deviations from the legality of the transfer of land rights in the form of procedures, material requirements and formal requirements, resulting in the land transfer being invalid and being canceled due to defects in administrative law through the Head of the Land Office.